Creativity Characteristics in Indonesian Elementary Students' Drawings: A Cross-Cultural Validation of Lowenfeld's Theory - Agus Tri Sudanayasa; Yun Ratna Lagandesa; Kadek Hariana; Rizal Rizal; Kasmawati Kasmawati (Papanda Publisher, 2026)
This study investigates creativity characteristics in elementary school students' drawings through the framework of Viktor Lowenfeld's artistic development theory. Despite extensive research in Western contexts, limited empirical evidence exists regarding children's artistic development in Indonesian elementary schools, particularly concerning how visual elements reflect developmental stages. A qualitative descriptive approach was employed to analyze ten drawings produced by second-grade students at SDN 1 Petobo, Central Sulawesi, Indonesia, during the 2025/2026 academic year. Data were collected through systematic observation of student artwork, semi-structured interviews with teachers and students, and photographic documentation, then analyzed using Miles and Huberman's continuous comparative method focusing on line quality, form characteristics, spatial organization, and color application. Findings reveal that students consistently exhibited schematic stage characteristics including stable visual schemas, baseline spatial organization, geometric form simplification, and representational color usage. Unexpectedly, several students demonstrated nascent depth representation techniques typically associated with later developmental stages, suggesting that contemporary educational environments may accelerate certain artistic competencies. Individual variations in compositional complexity and narrative elaboration were observed within the overall schematic consistency. This research validates Lowenfeld's framework cross-culturally while demonstrating that Indonesian elementary students' artistic development aligns with established developmental patterns, contributing empirical evidence to the literature on children's creativity in non-Western educational contexts and supporting developmentally appropriate art pedagogy.